Development Production Process Cellulose from Rice Straw - Krisnayana, Rina; Nugroho, Gunawan; Biyanto, Totok Ruki (Journal of Ecohumanism, 2025)
Biomass The largest in Indonesia is rice straw, where content the largest is cellulose. Cellulose the beneficial in industry biomedicine, energy, and electronics. In this research, we develop a production process for cellulose with a novelty is multistage method are first-stage crusher mechanical 5000 rpm, stage 2 hydrolysis NaOH and stage 3 delignification with NaClO2. The aim is get maximize the mass of cellulose and investigate the interaction between 3 factors design that is NaOH concentration, temperature reaction and reaction time its effect on cellulose mass. This research provides results that by using the method multistage, cellulose was successfully obtained from rice straw. Mass model cellulose in the production process cellulose to be used in the optimization stage is quadratic. Optimization of mass cellulose from rice straw using RSM (response surface methodology), algorithm genetics, and PSO method. Optimum mass cellulose at NaOH content = 7%, temperature = 80 ⁰C, and reaction time = 5 hours. Characterization morphology through scanning microscope electron (SEM) shows the formation cellulose shaped stem. FTIR shows group its function is group hydroxyl, CH group, band on CO group and characteristics of β-glycosidic bonds. Diffraction X-rays (XRD) reveal that cellulose has a crystallinity of 63.2% and analysis thermogravimetry (TGA) shows that % heavy experiences degradation as it rises temperature, where cellulose experiences degradation at temperature around 250⁰C and after 350⁰C, the remaining residue decomposes at a slow degradation rate.